The impact of surface currents on the wave climate in narrow fjords. (December 2021) - Christakos, Konstantinos; Björkqvist, Jan-Victor; Breivik, Øyvind; Tuomi, Laura; Furevik, Birgitte R.; Albretsen, Jon
Abstract: This study investigates the effect of surface currents on wind-generated waves in a complex coastal system with narrow fjords. The simulations are based on a phase-averaged wave model forced with surface currents from a high-resolution coastal ocean and fjord circulation model, and high-resolution winds from a nested atmospheric model. Wave simulations with and without ocean forcing are evaluated by comparing integrated wave parameters and modelled spectra with observations from five wave buoys. The comparison covers three winter seasons (2017–2020) and a case study. The wind sea part of the spectrum is better simulated at all locations when using the current forcing. At the most sheltered location, where wind sea dominated the wave climate, the wave height estimates improved by 12 percentage points when including current forcing. Spectral moments and the shape of the average spectra are also improved at most of the locations when current forcing is applied. The effect of wave–current interactions was found to be more pronounced at inner locations where the relative difference of spectral bandwidth is up 5%, the difference in directional spreading is greater than 5 degrees during strong surface currents, and the relative difference in peak frequency is exceeding 10%. Our results are consequential for narrow, deep and sheltered water bodies, but are not expected to carry over to shallow water areas. Highlights: Wave simulations at inner fjords significantly improve by using the ocean forcing. Ocean forcing improves the simulations of the wind sea at exposed locations. Ocean forcing changes the spectral bandwidth and directional spreading.